La región económica - Boudeville, Jacques R. (1959)
The author exposes Concepts, principles and methods of regional investigation and, principally, its operational aspect. He treats the methods of analysis of a determined region and those fore ordained to obtain individual and collective cooperation as regards to development and safeguard of resources of the whole region. He duly makes clear the conception of a decentralized and coordinated planification, all with the aim of making the panorama clear and being a guide to those who might be interested in a cooperative effort, destined to extend and coordinate regional activities in both, technical and practical aspects